Validation of a Blood Stability Score as an easy‐to‐use blood sample quality index. (30th August 2016) - Robinson, N.; Kirchbichler, A.; Banuls, O.; Mader, M.; Aikin, R.; Sottas, P.‐E.; D'Onofrio, G.
Summary: Introduction: The athlete biological passport (ABP) was implemented based on conservative requirements on sample storage and transport to ensure blood integrity. Blood remains stable over periods longer than the currently employed time limits. We investigated whether time and temperature requirements for sample storage can be used in a flexible model rather than based on fixed limits. Methods: A literature review was performed analyzing the stability blood variables. A Blood Stability Score (BSS) was derived to integrate the direct dependence of the degradation rate on temperature. A validation study was then carried out in real testing conditions with antidoping blood samples. Upon sample reception, a full blood count was obtained, and then again after refrigeration for an extended period. Results: A BSS formula integrating storage temperature (T) and collection to analysis time (CAT) was developed: BSS = CAT + 3 × T. In real testing conditions, negligible differences were observed for some variable as BSS values approached a score of 95, while no difference was observed in HGB and RET%. Conclusion: This study confirms that samples can be transported for longer periods and that the adaptive time and temperature approach as formalized in a rule that the BSS should not exceed 85 guarantees the stability of RBC variables used in the ABP.